The Use of The Heuristic Approach to Improve The Listening Ability of Middle School Students - Yunita Yunita; Abdullah Abdullah; Wayan Satria Jaya; Adenan Damiri (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2019)
This study aims to increase learning activities by applying a heuristic approach to learning to improve listening ability and learning activities for Class VIII students at SMP Negeri 2 Trimurjo in the 2018/2019 academic year by applying a heuristic approach. This research method is Classroom Action Research (CAR). Data collection techniques in research are observation, documentation, and tests. The technique used in this research is a written test technique, which is to obtain data from the test results of each cycle. Based on the analysis of observational data. There is an improvement in listening ability through a heuristic approach in class VIII SMP Negeri 2 Trimurjo in the 2018/2019 academic year. Therefore, student activity has achieved an indicator of student activity success increasing at least well.